Dinners and their objective points - Roberts, William Harry (My University, 1899)
Introduction: The time for taking food, the selection, preparation, and proper distribution of it in appropriate meals are questions of considerable importance, notwithstanding the fact that they have ever been influenced by the caprices of fashion and the artificial habits of man. How much they have had to do with the modification of the human species and even the extinction of whole races of men is certainly a problem of much interest. Man in his savage condition, feeds with great irregularity. When he finds food plentiful, he eats from morning till night and knows on other pleasure than that of eating, drinking and sleeping.
Citation: Roberts, William Harry. Dinners and their objective points. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Ancient Dinners; Roman Dinners; Nut ritive Value of Foods; Theses; Manuscripts (documents)